Decreased placental IL9 and IL9R in preeclampsia impair trophoblast cell proliferation, invasion, and angiogenesis - Yi Sun; Siyu Liu; Rong Hu; Qiongjie Zhou; Xiaotian Li (Taylor & Francis Group, 2020)
Objective Our study aimed to investigate IL9 and IL9R expression in preeclampsia and assess their effects on trophoblast biological behaviors. Methods IL9 and IL9R expression of placenta tissue were evaluated by immunochemistry and q-PCR. Using transwell, CCK-8, and tubule formation assays measured invasion, proliferation and angiogenesis of trophoblast with adding IL9 or anti-IL9R antibody. Results IL9 and IL9R levels were significantly decreased in preeclampsia. IL9 improved trophoblast activities. Blocking IL9/IL9R resulted in decreased proliferation, invasion, and tube-formation capability of trophoblast. Conclusions IL9 and IL9R contribute to the pathogenesis of preeclampsia. IL9/IL9R signaling provides a new potential therapeutic target for preventing preeclampsia.